PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTU MULTIREPRESENTASI TERHADAP KEMAMPUAN PENALARAN SISWA PADA KONSEP PENCEMARAN LINGKUNGAN DI KELAS X - Guntur Nurjaman; Anna Fitri Hindriana; Haruji Satianugraha (Quagga : Jurnal Pendidikan dan Biologi, 2018)
The purpose of this study was to analyze the effect of the application of the PBL (Problem bassed Learning) on the ability of reasoning. The method used in this study was Quasi Experimental Design. The population in this study is all students of class X in one of the SMAN have accreditation A in Kuningan District Year 2016/2017 School of 195 students. Sampling was conducted using cluster random sampling technique, divided into two groups, namely grade class model of PBL (Problem bassed Learning) class of 39 students and discussion method 39 students. The instrument used in this research is the test description of students' deployment ability, student questionnaire and observation sheet. Hypothesis testing using parametric statistical tests in this case to test the hypothesis that the effect of the application of the model-assisted PBL multirepresentasi against reasoning abilities using the t test obtained that t t table is 3.63 2.67, which means there is a good influence on the implementation of the model PBL (Problem bassed Learning) who assisted multirepresentasi against reasoning ability of students to the concept of environmental pollution. Therefore it can be concluded that the students reasoning ability is increased when used models multirepresentasi PBL assisted in the learning process.Keywords: Model PBL (Problem Based Learning), Reasoning Ability, Mul tirepresentas